MOTIVASI BELAJAR PENDIDIKAN AGAMA HINDU SISWA SMK NEGERI 5 DENPASAR PADA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19: MOTIVASI BELAJAR PENDIDIKAN AGAMA HINDU SISWA SMK NEGERI 5 DENPASAR - I Kadek Arta Jaya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The development of the world of education in Indonesia today is still experiencing various problems and challenges. One of the most recent challenges faced is due to the outbreak of the COVID-19 virus, which causes the entire learning system in educational institutions to experience a change from face-to-face learning to distance learning or to be transferred into the learning process to online or online learning methods. The disruption of the learning process causes several changes to occur in students which in turn also affect their learning motivation. This study uses quantitative research methods, using the sampling technique used is accidental sampling. The population in this study were all students of class XI SMK Negeri 5 Denpasar who participated in the online or online learning process. The data analysis method used in this research is using the Mann Whitney U analysis method. This type of research is a quantitative research combined with qualitative in explaining the results of the analysis of the learning motivation of students. The theoretical foundation in this research is the theory of learning motivation and the aspects that influence learning motivation. The results of this study indicate that the significance value of the Mann Whitney U is 0.000, which means the motivation to learn Hindu religious education in students who take online or online learning in the midst of the COVID-19 pandemic situation has decreased, because the significance value of 0.000 is less than 0.05 ( p <0.05).